Evaluation of educational interventions to assess preventive behaviors, perceived barriers and cause to action for Golestan province people regarding Covid-19 in 2020 - Mansoureh Moradi, Nahid Jafari Bidhendi, Fatemeh Jafarian , Nasimeh Najafi, Zahra Haji Ebrahimi, Talia Chitsaz (Drugs and Cell Therapies in Hematology, 2021)
Background and Aim: Covid-19 disease is an emerging viral disease that has caused a pandemic in the world. Due to lack of vaccines and definitive treatment for this disease, preventive measures and behaviors are the only way to prevent this disease. Preventive measures such as education are one of the most important prevention and control strategies. After providing education, the evaluation of community-based interventions is a fundamental step towards reforming and guiding programs toward the goals of the health system. The aim of this study was to measure the preventive behaviors of Covid-19, perceived barriers and cause to action of Golestan province people. This study is a descriptive-analytical study that was conducted cross-sectionally. Methods: The present study was conducted with a researcher-made questionnaire via telephone interviews among 600 people aged 20-70 years in the province. Results: In the present study, the mean score of desirable behavior was (37.15 out of 42) and there was a need for more educational intervention regarding the use of masks in public places (p = 0.00). The most reported barrier was "I cannot stay home due to my job" (21%). In the cause to action section, people selected television and radio as the source of receiving messages (88%). Conclusion: The desirability of preventive behaviors can confirm the health system’s efforts to inform and improve attitudes and skills training and indicates the need for more intervention by other sectors with the SDH approach to remove perceived barriers.